2022
DOI: 10.11591/ijece.v12i3.pp3033-3043
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of image resampling using correlation aware convolution neural networks for image tampering detection

Abstract: <span>Detecting hybrid tampering attacks in an image is extremely difficult; especially when copy-clone tampered segments exhibit identical illumination and contrast level about genuine objects. The existing method fails to detect tampering when the image undergoes hybrid transformation such as scaling, rotation, compression, and also fails to detect under small-smooth tampering. The existing resampling feature extraction using the Deep learning techniques fails to obtain a good correlation among neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The work has used a total of three datasets; in this first, the image is resized to into the non-overlapping region of similar to the work presented in [17]; thus, induces certain artifacts. In [17] used space-filling curve for extracting correlation among both horizontal and vertical streams; the model achieved good, tampered region detection accuracies; however, with poor segmentation accuracies; especially under small-smooth hybrid attacks.…”
Section: B Preprocessingmentioning
confidence: 99%
See 3 more Smart Citations
“…The work has used a total of three datasets; in this first, the image is resized to into the non-overlapping region of similar to the work presented in [17]; thus, induces certain artifacts. In [17] used space-filling curve for extracting correlation among both horizontal and vertical streams; the model achieved good, tampered region detection accuracies; however, with poor segmentation accuracies; especially under small-smooth hybrid attacks.…”
Section: B Preprocessingmentioning
confidence: 99%
“…The work has used a total of three datasets; in this first, the image is resized to into the non-overlapping region of similar to the work presented in [17]; thus, induces certain artifacts. In [17] used space-filling curve for extracting correlation among both horizontal and vertical streams; the model achieved good, tampered region detection accuracies; however, with poor segmentation accuracies; especially under small-smooth hybrid attacks. In addressing the segmentation problem, this paper introduces an improved CNN model that with an additional layer to obtain a good correlated features-map for achieving improved tampered region detection and segmentation outcome.…”
Section: B Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…The inception module in a parallel manner uses 3 × 3, 5 × 5, 1 × 1, and max pooling filters. The improvised model achieves a better MS lesion segmentation outcome than the standard CNN model [32,33]. In [28] showed that the UNET architecture are very good in performing segmentation of tumor in Kidney using CT images.…”
Section: 1mentioning
confidence: 99%